Supplier Intelligence In MRO Procurement - Jeeva, Ananda (IEEE Intelligent Transport Systems Society (IEEE/ITSS), 2008)
This paper explores the requirements for long term sustainable procurement practices. In the procurement of very expensive plant and equipment, MRO and the very long term continued availability of parts and components is very critical. Sustainable procurement practices are also critical in the continued non-disruption of critical parts and components in a manufacturing process. It proposes that procurement personnel and practices must have appropriate information and data of their prime suppliers of critical components, sub-assemblies and parts. Current research and literature search indicates there is very little publication and research investigating supplier intelligence (SI) in the context of the suppliers' suppliers' financial health, corporate governance, operating environment, capability, capacity and basic long term survival. This paper proposes the need for a conceptual model for gathering supplier's suppliers' intelligence for long term supplier relationship management; negotiation and contract management. The impetus for such information of a trading partner is becoming more critical since the collapse of large multi national corporations. Supplier intelligence is a fitness evaluation that enables the buyer to operationalise their long term procurement strategies with more certainty and lower risk. This paper also proposes how long term contractual terms and conditions may be designed taking into consideration of supplier's suppliers' profile to build superior supply chains and increase competitive advantage, hence a sourcing strategy.